2019
DOI: 10.3389/fmicb.2019.00894
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Multiple Vibrio parahaemolyticus Virulence Factors by Citral

Abstract: Citral was known as a widely used food additive with antimicrobial activity; however, whether it can be a potential therapy for controlling bacterial virulence with less risk of antimicrobial resistance remains to be investigated. Herein, we demonstrated that Vibrio parahaemolyticus virulence factors that contribute to infection were effectively inhibited to different degrees by sub-inhibitory concentrations (3.125, 6.25, and 12.5 μg/ml) of citral. Citral exerted strong inhibition of aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…In another study, 0.2 µg/mL of citral significantly inhibited mixed biofilm (S. aureus and S. enterica) formation, which could be caused by decreasing AI-2-mediated quorum sensing communication [35]. The inhibition of AI-2 production by citral treatment was demonstrated by [36]. Our results also proved that citral significantly inhibited both biofilm formation and bacterial communication via AI-2; however, the inhibition of quorum sensing based on AI-1 was more effective and to our knowledge, this is the first report on such activity.…”
Section: Discussionmentioning
confidence: 93%
“…In another study, 0.2 µg/mL of citral significantly inhibited mixed biofilm (S. aureus and S. enterica) formation, which could be caused by decreasing AI-2-mediated quorum sensing communication [35]. The inhibition of AI-2 production by citral treatment was demonstrated by [36]. Our results also proved that citral significantly inhibited both biofilm formation and bacterial communication via AI-2; however, the inhibition of quorum sensing based on AI-1 was more effective and to our knowledge, this is the first report on such activity.…”
Section: Discussionmentioning
confidence: 93%
“…RT-qPCR was performed in a 25 μL reaction volume using SYBR Green Master Mix (Takara) on a StepOne™ Real-Time PCR system (ABI, Foster, CA, USA). The cycling parameters included an initial denaturation at 95 °C for 3 min, followed by 45 cycles of 95 °C for 5 s, 60 °C for 30 s, and primer extension at 72 °C for 30 s. The samples were analyzed in triplicate, and the relative gene expressions were analyzed with the 2 -ΔΔCT method, as previously described [ 28 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Chlorinated disinfectants are widely applied in the food industry; among them, sodium hypochlorite (NaOCl) is easy to access and always compatible with other detergents. Kwan [140] found that 5 min blue light (440 nm) irradiation while in combination with NaOCl obtained increased reduction of Enterococcus faecalis biofilm adherence. Other potential disinfectant applications involve electrolyzed water and cold plasma treated water, which exhibit antibiofilm capacities and are considered as hurdles.…”
Section: Chemical Disinfectantsmentioning
confidence: 99%